Heroes, History, and Two Nationalisms: Jacques Cartier - Gordon, Alan (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1999)
AbstractHistorical heroes are created to represent particular social and political goals. Jacques Cartier is a case in point. He is really a nineteenth century figure. Although he lived in the sixteenth century, he was unremembered before the 1830s. Thus, he is a product of nineteenth-century scholarship, attitudes, and biases. Moreover, Cartier's historical meaning shifted over the course of some four decades from a religio-national affirmation to a symbol of cultural ties. Similarly, his historical context shifted; Jacques Cartier was never fixed in historical memory. In 1835, and again in 1889, Cartier was portrayed as the discoverer of Quebec, and in particular of Quebec City. By the 1930s, his significance had broadened to the discovery of Canada, with differing interpretations as to what that meant. But historical heroes are not rooted in reason. They are rooted in lived experience, or more precisely, in lived noumenal experience. The veneration of heroes is more emotional than rational.